PERANAN KOMISI NASIONAL HAK ASASI MANUSIA DALAM PERADILAN PIDANA (Faculty of Law, University of Palembang, 2023)
The aim of the research is to determine the role of Komnas HAM if serious human rights violations occur in the criminal justice system. This work is based on normative legal methods, i.e. The applicable legislation is currently being studied. The data used in this research are: Secondary data, namely. materials obtained from library research, consisting of: primary legal materials, secondary legal materials, tertiary legal materials. The results of the investigation show that Komnas HAM acts as an investigator of serious human rights violations and the investigation is carried out by the Attorney General's Office. This separation of research and investigative duties also creates problems in the relationship between these two institutions when resolving important human rights cases.